From information capture to knowledge dissemination: how to meet the stakeholders' information needs - Lopes, I. T. (The Journal of Knowledge Economy & Knowledge Management, 2009)
Traditional value chain, whose scope of application is essentially industrial, has ceased to be meaningful. They have been replaced by new business models (strongly developed through electronic platforms), structured around powerful “networks”. Sharing information, the use of communal structures, the speed of technological developments, the heightened use of resources, and its modular nature, instils strategies in this type of company which are based on a capacity to anticipate, innovate and make shared use of opportunities. Knowledge management is dominated by the applications of the second industrial revolution conquests and technological revolution, where information, aggregated to communication technologies, assumes a basic role in the sustainable development and in the company’s level competitiveness. While marked by connectivity, information, convergence and mobility, knowledge management will be expressed, independently of the perspective analysis, in a strong and deep cultural transformation inside the companies and their relation with stakeholders. This is the genesis of an Electronic Knowledge Management Culture (EKMC). Based on fifty-one companies, most of them integrating the Euronext Lisbon Indexes, we have explored the typology of information (voluntary and non-voluntary) effectively released to stakeholders through corporate websites. Size of companies and net returns seems to contribute positively for the quality and quantity of information effectively disseminated.